The Influence of Village Financial System, Clarity of Budget Targets and Transparency on Accountability of Village Fund Management - Anwar, Khairil; sulkiah, Sulkiah; Wadi, Ikhwan (E-Jurnal Akuntansi; Vol 34 No 9 (2024)DO - 10.24843/EJA.2024.v34.i09.p05, 2024)
This study aims to determine the effect of the village financial system, clarity of budget targets, and transparency on the accountability of village fund management in villages in Pringgabaya District, East Lombok Regency. The number of samples was 75 people determined using the purposive sampling method. Data were collected through the questionnaire method. The analysis technique was carried out using multiple linear regression analysis. The results of the study indicate that the village financial system has a positive effect on the accountability of village fund management. Clarity of budget targets has a positive effect on the accountability of village fund management. Transparency has a positive effect on the accountability of village fund management. Keywords: Village Financial System, Clarity of Budget Targets, Transparency, Accountability of Village Fund Management